Accountant’s Ethical Orientations Under Ethical Decision Making Literatures Review Of Accounting’s Aspect From 1995 To 2012 - Winata, Suryadi; Limajatini, Limajatini (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2020)
The objective of this study is to invent ethical judgments of Accountants from 1996 - 2013. The research’s used O’Fallon and Butterfield, 2005 about empirical ethical orientations from 1994 to 2004, and Craft review 2013 also from 2005 to 2012. Research method used in this study is the literatures base on the reviews of empirical ethical decision making. Code of ethics and ethical education affect the ethical orientations of accountants in practice, and empowered idealism Dan relativism (ethical philosophy). The implementations of an ethical climate in business step by step would strengthen ethical decisions made by accountants in practice.